2022
DOI: 10.3389/fmicb.2021.801152
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing the Veterinary Antibiotic Apramycin for Antibacterial and Antibiofilm Activity Against Pseudomonas aeruginosa From Cystic Fibrosis Patients

Abstract: Objectives:To evaluate the in vitro antibacterial, antibiofilm, and antivirulence activities of apramycin, comparatively to tobramycin, against a set of P. aeruginosa from chronically infected cystic fibrosis (CF) patients.MethodsThe activity of antibiotics against planktonic cells was assessed by performing MIC, MBC, and time-kill assays. The activity against mature biofilms was evaluated, in a microtiter plate, both in terms of dispersion (crystal violet assay) and residual viability (viable cell count). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…After incubation, planktonic cells were removed, and the attached cells were washed three times with PBS. As evidenced in earlier reports, 48-hour incubation in high nutrient medium is sufficient to form a mature biofilm by Pseudomonas isolates [ 31 , 32 ]. The biofilm was stained with 0.1% (w/v) crystal violet.…”
Section: Methodsmentioning
confidence: 60%
“…After incubation, planktonic cells were removed, and the attached cells were washed three times with PBS. As evidenced in earlier reports, 48-hour incubation in high nutrient medium is sufficient to form a mature biofilm by Pseudomonas isolates [ 31 , 32 ]. The biofilm was stained with 0.1% (w/v) crystal violet.…”
Section: Methodsmentioning
confidence: 60%
“…S1, available in the online version of this article) [9,10]. Due to this characteristic, apramycin is not impacted by other aminoglycosides' resistance mechanisms and has the potential to be used in the treatment of MDR strain infections [11,12]. Moreover, in one study, apramycin showed potent bactericidal activity against Mycobacterium abscessus, and the strains tested were 100 % susceptible to apramycin in vitro [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Both apramycin and cefotaxime have been declared ‘critically important’ for human medicine and trimethoprim ‘highly important’ by the WHO (World Health Organization, 2019 ). Moreover, apramycin has been shown to be effective against highly drug‐resistant strains of P. aeruginosa (Kang et al, 2017 ), including those isolated from cystic fibrosis patients (Di Bonaventura et al, 2022 ) and cefotaxime is used in aquaculture to treat P. aeruginosa infections (Ali et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%